Path Coefficient Analysis of Yield Components of Rice under Normal and Aerobic Conditions - Chandra, Khushboo; Nilanjaya (International Journal of Bio-resource and Stress Management, 2017)
Selection for yield parameters is often difficult in crop breeding because yield is a complex inherited character controlled polygenically, contributed by several component traits. Twenty five genotypes of rice were evaluated under aerobic and normal conditions to study the path coefficient analysis based on fifteen morpho-physiological traits. Path analysis revealed at genotypic level that under aerobic and normal condition traits like days to 50% flowering (0.487), no. of spikelets panicle-1 (0.572), number of tillers plant-1 (0.688), relative water content in flag leaf (0.98) and maximum root length (0.832, 1.18) had highest positive direct effect whereas, proline accumulation in leaves(-0.31) had high negative direct effect under normal condition and these important plant traits must be taken into consideration when further breeding program for higher yield in rice under aerobic and normal conditions is to be planned. Characters like days to fifty percent flowering, relative water content, maximum root length and proline were noticed to exert high direct effects on grain yield plant-1. Panicle length showed positive association with number of spikelets panicle-1, 1000 grain weight and grain yield per plot, whereas it showed negative correlation with proline accumulation in leaves under both conditions. Hence, these traits may be helpful in selection of suitable parents for future breeding programmes. Grain yield per plot showed negative and non-significant association with days to fifty per cent flowering under control condition indicating early maturing genotypes should be preferred under water limited condition. It indicated that earliness enabled the cultivars to escape drought at the end of the growing season under water stress condition. High indirect effects of most of the traits were noticed mostly through panicle characters indicating importance of the trait as selection criteria in crop yield improvement programs.